قاعدة الخراج بالضمان وتطبيقاتها في المعاملات المالية - محمد الأمين, بن أحمد; حيدر, بوعافية; عبد الكريم, بركبية (University of Eloued-جامعة الوادي, 2022)
يدرس هذا البحث أحد أهم القواعد الفقهية؛ ألا وهي قاعدة "الخراج بالضمان" من خلال التعريف بها، وبيان أدلتها، وحجيتها من الكتاب والسنة، وبيان عدد من تطبيقاتها في بعض أبواب المعاملات المالية، كالبيوع This research studies one of the most important rules of jurisprudence; Namely, the principle of “charging with security” by introducing it, explaining its evidence, its authenticity from the Qur’an and Sunnah, and clarifying a number of its applications in some sections of financial transactions, such as sales and leasing والإجارة.
مذكرة ماستر
Keywords: . قاعدة . ضمان . الفقه; Base . a guarantee . jurisprudence